Application of the Principle of Justice for the Health Social Security Administering Body in the Implementation of Health Insurance (Analysis Study of the Fulfillment of the Rights of BPJS Health Participants in Tegal Regency) - Azda Aulia Fajri; Y. Budi Sarwo (Universitas Katolik Soegijapranata Semarang, 2022)
Abstract: The Health Social Security Administering is a public institution mandated by the President as the organizer of Social Security, including the health sector. In practice, The Health Social Security Administering carries out its duties by referring to the principles regulated in Law Number 36 of 2009 concerning Health. The principle of justice is important so that every community can obtain health services as a whole without discrimination. Remembering the fifth precept of Pancasila as the basis of the state to regulate social justice for all Indonesian people. So that discrimination in health services must be eliminated. The purpose of this study was to examine and analyze the application of The Social Security Administering principle of justice to the fulfilment of participants' rights in health insurance, its efforts and obstacles in Tegal Regency. The research method used in this research is sociological juridical, namely research that examines empirical or real conditions in society regarding the application of the law, especially health law, organized by The Health Social Security Administering.The results of this study are the application of the Health Social Security Administering principle of justice to the fulfilment of the rights of participants in health insurance in Tegal Regency shows that it is still not optimal due to the supply of drugs for certain diseases that cannot be covered by the Health Social Security Administering and inadequate operating facilities in hospitals. Efforts are made to apply the principle of justice in the form of hospital innovation or from the Health Social Security Administering in health services by referring to Law Number 36 of 2009 concerning Health. Constraints are faced in the form of inadequate facilities and infrastructure in the operation of the hospital. In addition, the Health Social Security Administering participant patients who suffer from certain diseases and whose medicines are not covered in the INA-CBG's package must purchase at their own expense.Key Word: Principles of Justice, The Health Social Security Administering, Health Insurance. Abstrak: BPJS Kesehatan sebagai lembaga publik yang diamanahkan oleh Presiden sebagai penyelenggara Jaminan Sosial termasuk bidang kesehatan. Secara praktek, BPJS Kesehatan menjalankan tugasnya dengan mengacu pada asas-asas yang diatur dalam Undang-Undang Nomor 36 Tahun 2009 tentang Kesehatan. Asas keadilan sebagai asas penting agar setiap masyarakat memperoleh layanan kesehatan secara utuh tanpa unsur diskriminasi. Mengingat sila kelima dari Pancasila sebagai dasar negara mengatur keadilan sosial bagi seluruh rakyat Indonesia. Sehingga diskriminasi dalam layanan kesehatan harus ditiadakan.Tujuan penelitian ini adalah untuk mengkaji dan menganalisis penerapan asas keadilan BPJS terhadap pemenuhan hak peserta dalam jaminan kesehatan, upaya dan kendalanya di Kabupaten Tegal. Metode penelitian yang digunakan dalam penelitian ini adalah yuridis sosiologis, yaitu penelitian yang mengkaji keadaan empiris atau nyata dalam masyarakat tentang penerapan hukum khususnya hukum kesehatan yang diselenggarakan oleh BPJS Kesehatan.Hasil penelitian ini adalah Penerapan asas keadilan BPJS Kesehatan terhadap pemenuhan hak peserta dalam jaminan kesehatan di Kabupaten Tegal menunjukkan masih belum maksimal. Penyelenggaraan jaminan kesehatan secara totalitas bagi peserta Jaminan Kesehatan Nasional dengan tipekal peserta PBI maupun Non-PBI dengan peserta non JKN secara umum telah diperlakukan adil dan merata. Akan tetapi untuk peserta JKN ada pembatasan biaya plafon pada tindakan tertentu, kendala sarana, dan obat-obatan non formularium, mengakibatkan peserta JKN tidak bisa memperoleh pelayanan pengobatan yang maksimal. Upaya yang dilakukan dalam menerapkan asas keadilan berupa inovasi rumah sakit ataupun dari BPJS Kesehatan dalam layanan kesehatan dengan mengacu pada Undang-Undang Nomor 36 Tahun 2009 tentang Kesehatan.Kata Kunci: Asas Keadilan, BPJS Kesehatan, Jaminan Kesehatan